2010
DOI: 10.1007/s10734-010-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations among university students’ approaches to learning, regulation of learning, and cognitive and attributional strategies: a person oriented approach

Abstract: This study investigated the relationships among approaches to learning, regulation of learning, cognitive and attributional strategies, stress, exhaustion, and study success. University students (N = 437) from three faculties filled in a questionnaire concerning their self-reported study behaviour, cognitive strategies, and well-being. Their interrelations were examined in a variable-and a person-oriented way. Latent class clustering was used for clustering students into homogeneous groups. Three groups of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 50 publications
10
67
1
6
Order By: Relevance
“…When students agreed more with a reproductive conception of learning, they made more use of a surface approach to learning, they more often adopted an external regulation strategy, they attributed academic success more often to uncontrollable causes such as difficulty level of examinations, and they felt less selfefficacious than other students. Similar results were reported by Heikkilä et al (2011) in a study adopting a person-oriented approach among Finnish university students.…”
Section: Relations Of Learning Patterns With Personal Factorssupporting
confidence: 89%
See 3 more Smart Citations
“…When students agreed more with a reproductive conception of learning, they made more use of a surface approach to learning, they more often adopted an external regulation strategy, they attributed academic success more often to uncontrollable causes such as difficulty level of examinations, and they felt less selfefficacious than other students. Similar results were reported by Heikkilä et al (2011) in a study adopting a person-oriented approach among Finnish university students.…”
Section: Relations Of Learning Patterns With Personal Factorssupporting
confidence: 89%
“…Finally, they found that students who were doubtful about their own learning capacities tended to adopt an inadequate regulation strategy. Similarly, Heikkilä et al (2011) found significant relations between Finnish students' deep approach to learning and a selfregulated learning strategy, while there was no relation between self-regulation and a surface approach to learning. Richardson (2010) found a strong relation between students' conceptions and approaches among students in British distance education.…”
Section: Internal Relationships and The Dimensionality Of Learning Pamentioning
confidence: 88%
See 2 more Smart Citations
“…Існують збірки статей з особистісно орієнтова-ного навчання у медичній освіті [2]. Особистісно-орієнтоване навчання привертає увагу не лише вітчи-зняних, а й закордонних дослідників [3][4][5]. Проблема підготовки медичних сестер також викликає увагу дослідників, слід вказати на праці В. Лісового [6], О. Кравченко [7], М. Шегедин [8].…”
unclassified